The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/molecules24142590
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Immunoproteasome Inhibitors Using Large-Scale Covalent Virtual Screening

Abstract: Large-scale virtual screening of boronic acid derivatives was performed to identify nonpeptidic covalent inhibitors of the β5i subunit of the immunoproteasome. A hierarchical virtual screening cascade including noncovalent and covalent docking steps was applied to a virtual library of over 104,000 compounds. Then, 32 virtual hits were selected, out of which five were experimentally confirmed. Biophysical and biochemical tests showed micromolar binding affinity and time-dependent inhibitory potency for two comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The CovDock-VS was used in a virtual-screening protocol to find covalent inhibitors of the immunoproteasome's 5i subunit [ 54 ]. A commercial library of 100,000 boronic acids with desirable characteristics was screened in a multi-step procedure.…”
Section: Covalent Docking With Covalent-docking Programs: Methods And...mentioning
confidence: 99%
“…The CovDock-VS was used in a virtual-screening protocol to find covalent inhibitors of the immunoproteasome's 5i subunit [ 54 ]. A commercial library of 100,000 boronic acids with desirable characteristics was screened in a multi-step procedure.…”
Section: Covalent Docking With Covalent-docking Programs: Methods And...mentioning
confidence: 99%
“…181 Scarpino et al screened a large library of nonpeptidic boronic acid derivatives and identified compound 28 as a weak inhibitor of the immunoproteasome (IC 50 = 34 μM, Figure 9). 182 Further modification of this compound may provide a new generation of potent nonpeptidic proteasome inhibitors as chemotherapeutics. Similarly, Ladi et al designed compound 29 that showed remarkable in vitro activity against the β5 and β1 subunit of the immunoproteasome (β5i IC 50 = 4.1 nM; and β1i IC 50 = 0.85 nM).…”
Section: Peptide and Small Molecule Boronic Acids As Therapeuticsmentioning
confidence: 99%
“…Hits that were predicted to adopt a Ro19-like binding mode [105] were prioritized. Among the identified compounds, 1a (Figure 3; originally published as 1) is ranked the highest, as it shows modest affinity for β5i (IC 50 value for purified human iCP: 34 µM) and moderate selectivity over β5c (three-fold; Table 1) [85]. However, a complete cCP and iCP subunit selectivity profile has not been determined.…”
Section: • Boronatesmentioning
confidence: 99%